Venlafaxine as an Adjuvant Therapy for Inflammatory Bowel Disease Patients With Anxious and Depressive Symptoms: A Randomized Controlled Trial - Liang, Chang; Chen, Pingrun; Tang, Yu; Zhang, Chuheng; Lei, Na; Luo, Ying; Duan, Shihao; Zhang, Yan (Frontiers in Psychiatry, 2022)
Abstract Background and Aims: The effect of antidepressant therapy on Inflammatory Bowel Disease (IBD) remains controversial. This trial aimed to assess whether adding venlafaxine to standard therapy for IBD improved the quality of life (QoL), mental health and disease activity in IBD patients with anxious and depressive symptoms. Methods: A prospective, randomized, double-blind, placebo-controlled clinical trial was conducted. Participants diagnosed with IBD with symptoms of anxiety/depression were randomly assigned to receive either venlafaxine 150 mg daily or equivalent placebo and followed for 6 months. Inflammatory Bowel Disease Questionnaire (IBDQ), Mayo score, Crohn’s disease activity index (CDAI), Hospital Anxiety and Depression Scale (HADS) and blood examination were completed before the enrollment, during and after the follow-up. Mixed linear models and univariate analyses were used to compare groups. Results: Forty-five IBD patients were included, of whom 25 were randomized to receive venlafaxine. The mean age was 40.00 (SD=13.12) years old. 25 (55.6%) was male. Venlafaxine showed a significant improvement on QoL (p<0.001) and disease course (p=0.035), a greater reduction in HADS (anxiety: p<0.001, depression: p<0.001), Mayo scores (p<0.001) and CDAI (p=0.006) 6 months. Venlafaxine had no effect on IL-10 expression, endoscopic scores, relapse rate and use rate of biologics and corticosteroids, but did reduce serum level of ESR (p=0.003), CRP (p<0.001) and TNF-α (p=0.009). Conclusions: Venlafaxine has a significantly beneficial effect on QoL, IBD activity and mental health in IBD patients with comorbid anxious or depressive symptoms. (Chinese Clinical Trial Registry, ID: ChiCTR1900021496.)